2021
DOI: 10.3390/agronomy11071296
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Yield of Selected Herbaceous and Woody Industrial Crops across Marginal Agricultural Sites with Shallow Soil

Abstract: Agricultural land in Europe is affected by low rooting depth (LRD) on 27.9 Mha. This marginal agricultural land can potentially be used to grow industrial crops without directly threatening food security or biodiversity conservation. However, little is known about the yield performance of industrial crops at LRD conditions. This study therefore compiles and discusses the meaningful data available in scientific literature. Twelve relevant industrial crops were identified for Europe. Currently, robust informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Therefore, it should be thoroughly investigated whether such networks should become part of a permanent state-funded infrastructure in order to run as successfully as possible. It is true that there are already a large number of long-term field trials with industrial crops in the EU [140,141], some of which could be passed on from one project to the next. However, this is not the rule, with the consequence that many field trials cannot be monitored continuously over several years or, in the worst case, have to be abandoned despite their great potential for use as long-term studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it should be thoroughly investigated whether such networks should become part of a permanent state-funded infrastructure in order to run as successfully as possible. It is true that there are already a large number of long-term field trials with industrial crops in the EU [140,141], some of which could be passed on from one project to the next. However, this is not the rule, with the consequence that many field trials cannot be monitored continuously over several years or, in the worst case, have to be abandoned despite their great potential for use as long-term studies.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-three projects were identified and all the industrial crops examined in them were compiled (n = 48). 28 Industrial crops that were examined in at least four projects were classified as relevant. In total, 12 industrial crops were identified that meet this criterion (Table 1).…”
Section: Identification Of Most Relevant Industrial Crops In Europementioning
confidence: 99%
“…The suitability of industrial crops for LT conditions was conducted following previous studies by Ramirez-Almeyda et al 22 and Reinhardt et al 28 This evaluation scheme was based on the average level of biomass yield under limited growing conditions (here by LT) in relation to the biomass yield under non-limited growing conditions. Suitability levels range from 0 (unsuitable) to 4 (very suitable).…”
Section: Suitability Evaluationmentioning
confidence: 99%
“…and the society (due to rural development and low environmental impacts). However, reliable information is still scattered and not well organized to date because many experimental trials usually deal with different definitions of marginal lands and levels of agronomic input (Reinhardt et al, 2021a); hence, comparison among crops and expected results is often questionable. Therefore, the present study aims to present the large group of data obtained in the framework of the MAGIC project, to bring an advancement to knowledge on the suitability of certain industrial crops to marginal and contaminated soils, helping to clarify the constraints associated with their cultivation under low‐input practices.…”
Section: Introductionmentioning
confidence: 99%